Assessment of interactions and dosage recommendations of synthetic DMARDs - evidence-based and consensus-based recommendations based on a systematic literature search - Fiehn, Christoph; Leipe, Jan; Weseloh, C.; Bergner, Raoul; Krüger, K. (Zeitschrift für Rheumatologie, 2024)
Conventional synthetic (cs) and targeted synthetic (ts) disease-modifying antirheumatic drugs (DMARD) have potential interactions with a multitude of drugs. Furthermore, they sometimes have a lower therapeutic index, particularly in cases of limited organ functions. The aim of this work was to establish evidence-based recommendations on the therapeutic use of DMARDs in the context of drug interactions and dosage recommendations. A systematic literature search was carried out on the issue of drug interactions and dosages in cases of patients with limited kidney function and higher age and suffering from rheumatoid arthritis. A total of 2756 scientific publications were screened and 154 selected of which 68 were scrutinized in detail. Furthermore, the respective product information was also analyzed. A multitude of possible interactions of synthetic DMARDs with different drugs were detected, which were then assessed with respect to the clinical significance and consequences. A consensus process led to making recommendations with which the interactions were classified: A: dangerous combination, B: avoid combination (if possible, pausing DMARD treatment), C: possible combination requiring increased monitoring and potential adjustments in dosage and D: pharmacological interaction without relevance in DMARD standard doses. Apart from that dosage recommendations were established for each csDMARD and tsDMARD depending on kidney function and age. There are 3 primary recommendations and 11 core recommendations on interactions and dosages of csDMARDs and tsDMARDs meant as a practical help for therapeutic decision making and to improve safety in the treatment of rheumatoid arthritis.